2021
DOI: 10.1186/s12905-021-01445-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of sexual violence among adolescent girls and young women: findings from a cross-sectional study in a South African university

Abstract: Background Epidemiological data on the prevalence and factors associated with sexual violence is critical to understanding the magnitude of the problem and designing effective interventions. Drawing from cross-sectional data from a South African university, we examined the prevalence and correlates of sexual violence among adolescent girls and young women (AGYW). Methods We analysed data of 451 AGYW selected using stratified sampling. Sexual violen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 52 publications
2
8
1
2
Order By: Relevance
“…The results of the current study revealed that nearly three-quarters of the studied adolescent girls had been sexually harassed before; this finding is supported by Ajayi et al (34) who reported that nearly two-thirds of their study participants were sexually harassed. Meanwhile, other national studies reported a higher prevalence of sexual harassment phenomenon (Farouk & Hassan, El-Deeb, Roushdy & Sieverding and Fahmy & Badr (35,4,5,6) .…”
Section: Discussionsupporting
confidence: 85%
“…The results of the current study revealed that nearly three-quarters of the studied adolescent girls had been sexually harassed before; this finding is supported by Ajayi et al (34) who reported that nearly two-thirds of their study participants were sexually harassed. Meanwhile, other national studies reported a higher prevalence of sexual harassment phenomenon (Farouk & Hassan, El-Deeb, Roushdy & Sieverding and Fahmy & Badr (35,4,5,6) .…”
Section: Discussionsupporting
confidence: 85%
“… 31 The lifetime prevalence of sexual assaults reported among adolescents and university students in South Africa is high, at 37.9%. 32 Calls for urgent interventions to reduce the incidence of sexual assaults among college students should be heeded, while those who are already victims should be properly supported and rehabilitated.…”
Section: Discussionmentioning
confidence: 99%
“…Although most previous research has focused on the impact of domestic violence on women, a few studies have focused on the characteristics of adolescent girls and adult women who experienced sexual violence [ 6 ]. In Taiwan, no in-depth study has been conducted on this issue.…”
Section: Introductionmentioning
confidence: 99%